A STATISTICAL MIX-DESIGN APPROACH FOR ECOLOGICAL SELF-COMPACTING CONCRETE BASED ON RHEOLOGY AND PARTICLE PACKING - Nimodiya, Pareshkumar; Patel, Jigneshkumar M. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present paper puts forward a simple statistical mix design method for Self-Compacting Concrete (SCC) based on particle packing and targeted flow properties. Even for lower strength of concrete, high amount of binders are needed in production of self-compacting concrete (SCC) to satisfy the required rheological properties. Present research is intended to improve rheological properties of SCC by optimizing aggregate packing and thereby reducing binder content particularly for compressive strength 20-35 Mpa. For achieving this, a new simplified gradation based particle packing approach is used. Furthermore, a simplified mix design approach to produce SCC is given using proposed model. Using the proposed mix design approach, SCC mixes are casted with 20 mm and 10 mm maximum size of aggregate (MSA) and 300 kg, 320 kg cementitious material. For various mix proportions, V-funnel, sieve segregation, L box, compressive strength tests were performed. By present approach Fresh properties were improved as compare to existing SCC mix design approach without compromising compressive strength. The precision of the proposed model is at par with the present most efficient particle packing model (PPM). Moreover, modifications in EFNARC guideline are suggested.